Pengaruh Modal Intelektual Dan Struktur Modal Terhadap Nilai Perusahan Dengan Kinerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Periode 2020-2024 - Astrid Delvia; Berta Agus Petra; Olandari Mulyadi (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of intellectual capital and capital structure on firm value with financial performance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2024. The research population consisted of 251 manufacturing companies with a sample of 45 companies selected using purposive sampling technique. Data were analyzed using multiple regression analysis and path analysis with SPSS 23 software. The results show that intellectual capital and capital structure have a significant effect on financial performance. Capital structure and financial performance have a significant effect on firm value, but intellectual capital does not have a direct significant effect on firm value. Path analysis results indicate that financial performance successfully mediates the effect of intellectual capital on firm value with a total effect of 0.383, but fails to mediate the effect of capital structure on firm value. The adjusted R² values of 0.709 for the first equation and 0.469 for the second equation indicate that the independent variables can explain variations in the dependent variable by 70.9% and 46.9% respectively. This research provides practical implications for company management to pay more attention to intellectual capital development and optimal capital structure management in order to improve financial performance and firm value.